Effectiveness Problem Solving Techniques Through Group Guidance Services to Prevent Self-Injury Behavior in Adolescents - Al Mefa, Fadira; Syarqawi, Ahmad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to determine the effectiveness of problem-solving techniques through group guidance services in preventing self-injury in adolescents. The research method used is quantitative with a pre-experiment, one-group pretest, and posttest design. The data used in this research are primary and secondary. Secondary data was obtained from documentation, while primary data was obtained through a questionnaire with a Likert scale. The population of this study was class VII at MTs Islamiyah Hessa Air Genting, with as many as 63 people. The number of samples was eight people who had self-injury in the very high and high categories. The sampling technique uses a purposive sampling technique. The data analysis technique for testing the hypothesis uses the Wilcoxon Signed Ranks Test with an asymp significance value, Sig (2-tailed) of 0.012 (<), from a significance level of 0.05. This means that problem-solving techniques through group guidance services effectively prevent self-injury behavior in teenagers.